Assessment of multiple mycotoxins in raw milk of three different animal species in Nigeria. (January 2022) - Akinyemi, Muiz O.; Braun, Dominik; Windisch, Patrick; Warth, Benedikt; Ezekiel, Chibundu N.
Abstract: The mycotoxin profile of 135 raw milk samples from camel ( n  = 25), cow ( n  = 23) and goat ( n  = 87) in Nigeria was assessed by an ultra-sensitive LC-MS/MS method. Four, seven and 17 of the tested 36 mycotoxins were detected in camel, cow and goat milk, respectively. Among these were aflatoxin P1, alternariol monomethyl ether, citrinin, dihydrocitrinone, enniatins, ochratoxin α and sterigmatocystin reported for the first time in animal milk. The regulated aflatoxin M1 contaminated all cow milk (max: 81 ng/L) and 49% of goat milk (max: 3108 ng/L) samples, with 13% and 55%, respectively, exceeding the 50 ng/L EU limit. Aflatoxin M1 was not detected in camel milk samples. Overall, at least one mycotoxin was detected in 97% of all samples; beauvericin (87%) being the most frequent. Raw animal milk presents an additional source of mycotoxin exposures in the Nigerian populace. Consequently, mycotoxin mitigation should also target the dairy food chain. Highlights: Mycotoxins in 135 raw milk samples from camel, cow and goat were profiled. Camel, cow and goat milk contained 4, 7 and 17 mycotoxins, respectively. First report of AFP1, AME, CIT, DHC, enniatins, OTα and STER in animal milk. Animal milk is an additional multiple mycotoxin exposure source in Nigeria.